Essentials of computer organization and architecture - Null, Linda (Jones & Bartlett Learning, 2012)
Updated and revised with the latest data in the field, The Essentials of Computer Organization and Architecture, Third Edition is a comprehensive resource that addresses all of the necessary organization and architecture topics, yet is appropriate for the one-term course. This best-selling text correlates to the 2008 ACM-IEEE Computer Science Curriculum update and exposes readers to the inner workings of a modern